Case report: primary mediastinal germ cell tumour initially presenting as level IV cervical lymphadenopathy. (6th May 2019) - Crane, H.; Mustafa, S.; Tahir, F.; Brierley, D.J.
Abstract: This case report describes an unusual case of a primary mediastinal germ cell tumour presenting initially as lymphadenopathy in the neck. This case highlights the rare occurrence of germ cell tumours in an area common to the routine extra oral dental examination of lymph nodes.